The influence of initial selection age, relative age effect and country long-term performance on the re-selection process in European basketball youth national teams - Kalén, A.; Lundkvist, E.; Ivarsson, A.; Rey, E.; Pérez-Ferreirós, A. (Journal of Sports Sciences, 2021)
The aims of the study were to: (a) analyse the re-selection patterns in European youth basketball national teams, and (b) investigate how the chance of re-selection is influenced by the initial selection age and relative age of the players, as well as the long-term performance of the country at the youth level. The sample consisted of 8362 basketball players (5038 men, 3324 women) born 1988-1997 who have participated in at least one U16, U18 or U20 European youth basketball championship between 2004 and 2017. The results from the survival analysis showed that around 75% of male and 80% of female players participating in a championship were re-selected the following year. Also, initial selection age, relative age effect, and the country long-term performance influenced the re-selection rates, with relationships being different between men and women. To conclude, the results of the present study show that the re-selection process by which players progress in European youth national basketball teams is complex and influenced by several different factors.